MERAH BERPENDAR DI BRANG WETAN: Tegangan Politik 65 dan Implikasinya terhadap Industri Musik Banyuwangen - Ikwan Setiawan (Imaji, 2010)
This article discusses (1) creativities and complicated-tragic problems of Banyuwangen musicians, especially they who involved in Lekra (People Cultural Institution, the cultural organization of Indonesian Communist Party), during 1965 and some years later and (2) the development of Banyuwangen music industries after the bloody 1965. In Orla (Old Order), most of Banyuwangen musicians joined, culturally and ideologically, Lekra that had ideal promises to strengthen and empower people arts and cultures as the base for Indonesian culture. At post-1965, they experienced tragic life caused by regime’s surveillance mechanism towards cultural activities that were re assumed having relationship to communism. Fortunately, their friends from another cultural institutions helped and saved their life by arguing the government that they are cultural assets and very important for New Order regime. After 1965, the government to ensure disappearance of Leftist ideology guided Banyuwangen music industries. This development led to private music industries that produced and published Banyuwangen music in Melayu and kendang kempul instrument as the base of the recent development of Banyuwangen music industries. Key words: Lekra, communism, Banyuwangen music, recording industries